Feasibility Study on the Evaluation of the Dry Rubber Content of Field and Concentrated Latex of Para Rubber by Diffuse Reflectance near Infrared Spectroscopy. Issue 2 (April 2013) - Sirisomboon, Panmanas; Kaewkuptong, Apidul; Williams, Phil
The analysis of the dry rubber content (DRC) of Para rubber latex, including field latex and concentrated latex, using near infrared spectroscopy was conducted using a Fourier transform near infrared (FT-NIR) spectrometer in diffuse reflection mode over the wavenumber range of 4000–10, 000 cm −1 . The proposed method is useful for industrial purposes. The best model was developed using the partial least square regression (PLSR) from the spectra, which were pretreated using the 2 nd derivative method, where the correlation ( r 2 ), standard error of prediction ( SEP ) and bias were 0.997, 0.3398% and −0.0239%, respectively. The ratio of standard deviation ( SD ) to SEP of the reference data in the prediction sample set ( RPD ) was 18.18 and the ratio of the range to the SEP of the prediction set ( REP ) was 74.4. The model was validated using a new batch of samples and the prediction performance was good with an r 2 of 0.999, a SEP of 0.3898% and a bias of −0.0008%. Therefore, the NIR spectroscopy technique can be used as an accurate and rapid method for estimating the DRC of Para rubber latex for both field and concentrated latex.